Annual Report of the Economic and Social Commission for Asia and the Pacific 2023 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2023)
The Annual Report chronicles the United Nations Economic and Social Commission for Asia and the Pacific’s achievements and future goals, against a backdrop of major global shifts sweeping across the economic, social and environmental landscape. UN ESCAP promotes rigorous analysis and peer learning through its seven core areas of work: macroeconomic policy and development, trade and investment, social development, transport, statistics, environment and development, information communications technology and disaster risk reduction.